Density dependent responses in Southern Right whales Eubalaena australis at Península Valdés, Argentina - Crespo, Enrique Alberto (2015)
This paper presents information on rate of increase (RI) and mortality rates (MR) for Southern Right Whales (SRW). 1) RI was estimated using GLM procedures based on data of number of individuals obtained in aerial surveys carried out from 1999 to 2015 in Peninsula Valdes (PV). Predictor variables were Year and Julian Day, using also Julian Day2 . Response variables were: a) total number of whales; b) number of calves; c) number of solitary individuals and c) number of mating groups. The total population is increasing at 3.23% annually and the number of calves by 5.54%. RI declined from 6.22% (1999-2007) to 3.23 (1999-2014). Solitary Individual and Mating Groups are no longer growing, 2) the trend of MR was analysed trough time. Data of live and dead calves was obtained for the period 1971-1973, 1981-1982 and 2003-2014. The number of estimated calves born each year was obtained by means of a cumulative function developed from the GLM. It is clear that MR is variable among years. Maximum rates were observed in 2007, 2008 and 2009, being the highest rate in 2008 reaching almost 30% while minimum rates were as low as those observed in 2004 and 2014. The rates observed in the former years show the same pattern of variability with ranging 2- 10%. Finally, the analysis of the information supports that the SRW south Atlantic stock is increasing in the nursing area around PV. Although the number of whales in the surveyed area is increasing, RI is steadily decreasing. Density has been also increasing and whales are expanding their distribution to deeper waters and Golfo San Matías during the last decade. The analysis of the MR since the early 70´s shows an increase. All these facts together are coherent with a density-dependence response.